Structural Reorganization of Allyl Isothiocyanate into Pyrrole Ring under Superbase: A Straightforward Access to NH-2-(Alkylsulfanyl)-1H-pyrroles and N-Alkyl-2-(alkylsulfanyl)-1H-pyrroles - Nedolya, Nina A.; Brandsma, Lambert; Trofimov, Boris A. (Synthesis, 2013)
A novel and facile synthetic route to NH-2-(alkylsulfanyl)-1H-pyrroles and N-alkyl-2-(alkylsulfanyl)-1H-pyrroles is reported. This was achieved by deprotonation of allyl isothiocyanate with the superbasic pair lithium diisopropylamide and potassium tert-butoxide (1:1 molar mixture), followed by intramolecular ring closure, deprotonation of cyclic anion with a second equivalent of the superbase, and final sequential N-protolysis/S-alkylation or N,S-dialkylation of the formed N,S-centered pyrrol-2-ylsulfide dianion.
Keywords: 2-(alkylsulfanyl)-substituted pyrroles; allyl isothiocyanate; superbases; deprotonation; cyclization; alkylation